Konsep Keadilan dalam Perspektif Filsafat Hukum Islam - Amin, Mahir (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: This article discusses about the concept of justice in the perspective of the philosophy of Islamic law. Philosophically, there are two formulations of justice: first, the view that what is meant by justice is a harmony between the use of right and obligation are in line with the implementation of the proposition of âthe balance of lawâ or âthe dose of right and obligationâ; second, the view of the lawyers who formulate that justice is a harmony between legal certainty and proportionality of law. Justice, in Islamic law, is derived from the Most Just. It is because Allah SWT is the upholder of justice, then He must be believed not to apply unjust to His servants. The concept of justice, based on al-Shatibiâs maqasid al-shariâah theory, is determined by the benefits which are divided into three, namely daruriyyat (necessities), hajiyyat (needs), and tahsiniyyat (luxuries). This indicates that Islam is concerned with the issue of justice. The conception of justice will continue to evolve in line with the social development. Construction of law and justice in Islam cannot be separated from morality and transcendental beliefs since these aspects are intertwined.Keywords: Justice, philosophy, law, Islam.